Modeling Seasonal Variations of Sediment Transport and Morphological Changes in Delta Ecosystem: A Case Study of the Wulan Delta, Indonesia - Fadlillah, Lintang Nur; Widyastuti, Margaretha; Kim, Dong Hyeon; Marfai, Muh Aris (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
The suspended sediment from the Serang River plays a crucial role in the development of the Wulan Delta. This study employs the open-source DELFT3D model to investigate seasonal hydrodynamics, sediment distribution, and morphodynamic changes in the delta. Sediment dynamics during both the rainy and dry seasons were analyzed using the DELFT3D-Flow model. Tidal data were sourced from TPXO 9v1 and field measurements, while bathymetric data from GEBCO were validated against in-situ observations. Model results indicate seasonal sediment concentration patterns, which were further validated against satellite imagery, demonstrating consistency between simulated and observed sediment distribution. Statistical analysis revealed an RMSE range of 0.001 to 0.061. The estimated sediment deposition rate is approximately 1.2 t·yr⁻¹, with a deposition rate of 2.74 t·m⁻²·yr⁻¹ at both river mouths. About 12% of the sediment accumulates near the river mouth, while the remainder is redistributed by currents influenced by the Java Sea's bed morphology. Erosion was primarily observed in the eastern part of the delta and at the OWR mouth, whereas the western delta exhibited significant deposition due to strong river currents and substantial sediment supply. This sediment distribution suggests potential delta expansion from the west to the north. Findings contribute to the understanding of sediment transport processes in deltas, with implications for mitigating coastal erosion, enhancing delta resilience, and preserving ecosystems in similar regions across northern Java.